Gold-catalyzed post-Ugi alkyne hydroarylation for the synthesis of 2-quinolones - Xiaochen Du; Jianjun Huang; Anton A. Nechaev; Ruwei Yao; Jing Gong; Erik V. Van der Eycken; Olga P. Pereshivko; Vsevolod A. Peshkov (My University, 2018)
A series of propargylamides containing an electron-rich benzene ring was prepared via a Ugi four-component condensation. These adducts underwent gold-catalyzed intramolecular alkyne hydroarylation to efficiently construct the 2-quinolone core with N‑branched substituents. The method demonstrated broad substrate scope, high yields (up to 97 %), and favorable environmental profile using fluorinated alcohols as solvents.
Keywords: gold catalysis; hydroarylation; 2-quinolones; Ugi reaction